2006
DOI: 10.1002/app.24928
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoamine dendrimers as curing agents: The optimum polyamidoamine concentration selected by dynamic torsional vibration method and thermogravimetric analyses

Abstract: Polyamidoamine (PAMAM) dendrimers were investigated as curing agents in bisphenol A epoxy resin systems. The cure behavior of epoxy resin/PAMAM at varying components was investigated by a dynamic torsional vibration method (DTVM); the thermal behavior of the materials was characterized by means of thermogravimetric (TGA) analyses. The DTVM results show that 10/100 parts of the resin (phr) PAMAM was the optimum concentration for 1.0, 3.0, and 5.0 G PAMAM dendrimers/resin systems in our experiment. Also, the TGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Some authors [9,10] have used polyamido-amine dendrimers grafted onto silica as the curing agent in epoxy systems, and report increased thermal stability in comparison with the same epoxy cured with ethylene diamine (EDA), but there was no consensus on whether the glass transition temperature is increased or not. More generally, the reaction kinetics of bisphenol-A epoxy resins cured with polyamido-amine dendrimers has been studied [11,12], and it has been reported that, in comparison with the use of EDA as curing agent, the curing kinetics using polyester-amine dendrimers is very different, presenting two stages of cure and less heat of reaction [13]. The use of polypropylene-imine dendrimers as curing agents in epoxy systems is quite widely reported [14,15,16], and it appears that the molecular architecture of the dendrimers, in particular their steric hindrance and the number of attached –OH groups [14], greatly affects the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [9,10] have used polyamido-amine dendrimers grafted onto silica as the curing agent in epoxy systems, and report increased thermal stability in comparison with the same epoxy cured with ethylene diamine (EDA), but there was no consensus on whether the glass transition temperature is increased or not. More generally, the reaction kinetics of bisphenol-A epoxy resins cured with polyamido-amine dendrimers has been studied [11,12], and it has been reported that, in comparison with the use of EDA as curing agent, the curing kinetics using polyester-amine dendrimers is very different, presenting two stages of cure and less heat of reaction [13]. The use of polypropylene-imine dendrimers as curing agents in epoxy systems is quite widely reported [14,15,16], and it appears that the molecular architecture of the dendrimers, in particular their steric hindrance and the number of attached –OH groups [14], greatly affects the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tande et al [12] used ester-terminated poly(propyleneimine) dendrimers to plasticize polyvinyl chloride (PVC) with the decreased glass-transition temperature found, which is due to the additional free volume provided by the dendrimers. Other reports indicated that PAMAMs and these of similar molecular structures [13][14][15][16][17] could effectively crosslink epoxy resins. These dendrimers also exhibit the advantages of lowered vapor pressure, alleviated toxicity, reduced unfavorable odor, retarded carbonation in air, and improved compatibility with epoxy resins over the conventional linear-aliphatic-amine curing agents of low molecular weights (e.g., ethylenediamine).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can use small organic molecules and polymers as structural components, and thus acquire special physical and chemical properties. Up to now, dendrimers have been widely applied in many fields, such as supramolecular chemistry or host–guest chemistry,3, 4 electrochemistry,5 and photochemistry,6 nanoparticle synthesis,7–9 pollution management,10–12 dye decolorization,13, 14 preparation of monomolecular membranes,15–17 curing of epoxy resins,18, 19 catalysis,20–23 drug delivery,24–28 and gene transfection 29–31. Among them, the use of dendrimers in delivery systems has deserved more attentions in recent years 32, 33…”
Section: Introductionmentioning
confidence: 99%